Complex dielectric permittivity of films in the infra-low frequency range as studied by relaxation maps of thermally stimulated currents - Елена Алексеевна Волгина (Physics of Complex Systems, 2023)
The paper shows the possibility of interpreting the results of thermal activation spectroscopy of PVDF polymer films obtained by thermally stimulated currents of fractional polarization using the concepts of low-frequency dielectric spectroscopy. The paper presents the results of the study of temperature-frequency dependences of the components of complex dielectric permittivity in PVDF films with different degrees of orientation, polymorphic composition and pore percentage. It also provides the parameters of electrically active defects responsible for relaxation processes in the temperature range under study.